Adipose cell size: importance in health and disease - Stenkula, Karin G.; Erlanson-Albertsson, Charlotte (American journal of physiology. Regulatory, integrative and comparative physiology, 2018)
Adipose tissue is necessary to harbor energy. To handle excess energy, adipose tissue expands by increasing adipocyte size (hypertrophy) and number (hyperplasia). Here, we have summarized the different experimental techniques used to study adipocyte cell size and describe adipocyte size in relation to insulin resistance, type 2 diabetes, and diet interventions. Hypertrophic adipocytes have an impaired cellular function, and inherent mechanisms restrict their expansion to protect against cell breakage and subsequent inflammation. Reduction of large fat cells by diet restriction, physical activity, or bariatric surgery therefore is necessary to improve cellular function and health. Small fat cells may also be dysfunctional and unable to expand. The distribution and function of the entire cell size range of fat cells, from small to very large fat cells, are an important but understudied aspect of adipose tissue biology. To prevent dysmetabolism, therapeutic strategies to expand small fat cells, recruit new fat cells, and reduce large fat cells are needed.